Effects of the Indian National Health Insurance scheme (PM-JAY) on hospitalizations, out-of-pocket expenditures and catastrophic expenditures - Parmar, Divya; Strupat, Christoph; Srivastava, Swati; Brenner, Stephan; Parisi, Diletta; Ziegler-Wirtz, Susanne; Neogi, Rupak; Walsh, Caitlin; De Allegri, Manuela (Health systems & reform, 2023)
India launched one of the world's largest health insurance programs, the Pradhan Mantri Jan Arogya Yojana (PM-JAY), targeting more than 500 million economically and socially disadvantaged Indians. PM-JAY is publicly funded and covers hospitalization costs in public and private facilities. We examine how PM-JAY has affected hospitalizations and out-of-pocket expenditures (OOPE), and given the high use of private health care in India, we compare these outcomes across public and private facilities. We conducted a household survey to collect data on socioeconomic and demographic information, health status and hospitalizations for more than 57,000 PM-JAY eligible individuals in six Indian states. Using multivariate regression models, we estimated whether PM-JAY was associated with any changes in hospitalizations, OOPE and catastrophic health expenditures (CHE) and whether these differed across public and private facilities. We found that PM-JAY was not associated with an increase in hospitalizations, but it increased the probability of visiting a private facility by 4.6% points (p < .05). PM-JAY was associated with a relative reduction of 13% in OOPE (p < .1) and 21% in CHE (p < .01). This was entirely driven by private facilities, where relative OOPE was reduced by 17% (p < .01) and CHE by 19% (p < .01). This implied that PM-JAY has shifted use from public to private hospitalizations. Given the complex healthcare system with the presence of parallel public and private systems in India, our study concludes that for economically and socially disadvantaged groups, PM-JAY contributes to improved access to secondary and tertiary care services from private providers.
Gesehen am 10.11.2023
Keywords: Indien